Effect of Foliar Sprays with Nutrients and Growth Regulators on Seeding Vigour and Enzyme Activity in Mung bean - RITIKA BHASKAR; OMVATI VERMA; DK SHUKLA; VK SINGH; SK GURU (Seed Research, 2026)
The present study was undertaken tofind out the response of nutrient and growth regulators on seed germination, seedling vigour and enzyme activity of mung bean (Vigna radiata). Treatments consisted of three varieties viz.; Pant Mung 2 (small seeded), Pant Mung 4 (medium seeded) and Pant Mung 5 (bold seeded) and six foliar sprays; urea 2%, NPK 2%, DAP 2%, salicylic acid 100 ppm and indole butyric acid 100 ppm and control. Foliar spray of nutrients and growth regulators was done twice 40 and 55 days after sowing. The experiment was laid out in Randomized Block Design with three replications. After harvesting, seeds were used for conductinggermination test, seedling vigour and enzyme activities. Results revealed thatgermination percentage, seedling length,seedling vigour indices, protein content, á- amylase and protease enzymatic activity was recorded highest in bold seeded variety Pant Mung 5. Seeding vigour of mung bean was also influenced by foliar sprays of nutrients and growth regulators. Protein content in seeds increased significantly with 2% foliar spray of urea whereas, other quality parameters such as germination percentage, seedling length, seedling dry weight, seedling vigour index -I , seedling vigour index -II,á- amylase and protease enzyme activity were significantly higher in foliar spray of 100 ppm salicylic acid.